2020
DOI: 10.1080/23311932.2020.1796201
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adoption of major post-harvest handling practices of large cardamom in Nepal

Abstract: The ecological settings in the Himalayan hills provide a unique opportunity to the farmers in Nepal to sell their large cardamom in the global market. However, little efforts are made about the adoption of profitable large cardamom post-harvest upgrading practices in the country. This paper examines and discusses about the adoption of important post-harvest practices of large cardamom in the Eastern Himalayan road corridor of Nepal. Semi-structured interviews with 300 large cardamom-producing farmers as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In this study Seemingly Unrelated Regression (SUR) logit was used to better understand the important factors that affect the adoption decision of major orchard management practices of mandarin orange. The adoption decision is found to be influenced by the set of socio-economical, behavioral, institutional, and technical factors (Carrer et al, 2017;Career et al, 2019;Kattel et al, 2020). The dependent variables on the orchard management practices are binary and take the value Y j = 1 (for the adoption) and Y j = 0 (for otherwise); where (j=1,2......8) are the eight major orchard management practices devised for adoption by Prime Minister Agriculture Modernization Project (PMAMP), Citrus Zone office located in Gorkha.…”
Section: Empirical Framework Of the Studymentioning
confidence: 99%
See 3 more Smart Citations
“…In this study Seemingly Unrelated Regression (SUR) logit was used to better understand the important factors that affect the adoption decision of major orchard management practices of mandarin orange. The adoption decision is found to be influenced by the set of socio-economical, behavioral, institutional, and technical factors (Carrer et al, 2017;Career et al, 2019;Kattel et al, 2020). The dependent variables on the orchard management practices are binary and take the value Y j = 1 (for the adoption) and Y j = 0 (for otherwise); where (j=1,2......8) are the eight major orchard management practices devised for adoption by Prime Minister Agriculture Modernization Project (PMAMP), Citrus Zone office located in Gorkha.…”
Section: Empirical Framework Of the Studymentioning
confidence: 99%
“…Therefore, the Seemingly Unrelated Regression (SUR) logit model was used to identify the factors associated with the adoption of eight major orchard management practices. This was done by using the functional form of the logit model expressed by Gujarati (2009) and Kattel et al (2020).…”
Section: Empirical Framework Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In the same way, odds adoption of farmyard manure was 1.928 times more by respondents who received training compared to those who haven't received training. Kattel (2020) indicated that training dummy variable has a positive impact on farmers' decision on technology adoption.…”
Section: Regression Analysis Of Dependent and Independent/predictor Variablesmentioning
confidence: 99%